THE REVIEW OF OUTPATIENT PHARMACEUTICAL ACCOUNTING INCOME RECORDING AND VAT COLLECTION: A CASE STUDY OF HEALTH FACILITY ENTITY A - Setiadi, Fahmi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This study aims to review the recording of hospital outpatient pharmaceutical accounting income and the collection of value-added tax (VAT). The findings show that Hospital A is prone to both overstatements and understatements in recording outpatient pharmaceutical income for National Health Insurance Program (BPJS Kesehatan) patients, as the recorded amounts do not match the actual payments made by BPJS to the hospital. Such discrepancies may affect the calculation of output VAT determined by fiscal authorities. For stakeholders, the results provide a basis for formulating more equitable policies to ensure the sustainability of health facility entities. For the health facility entity, the findings can serve as a reference for tax planning strategies to minimize VAT-related risks on outpatient pharmaceutical products.